2021
DOI: 10.1016/j.omtn.2021.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA lnc_3712 impedes nuclear reprogramming via repressing Kdm5b

Abstract: Long non-coding RNAs (lncRNAs) are involved in shaping chromosome conformation and regulation of preimplantation development. However, the role of lncRNA during somatic cell nuclear transfer (SCNT) reprogramming remains largely unknown. In the present study, we identified 114 upregulated lncRNAs in the 8-cell SCNT embryos as candidate key molecules involved in nuclear reprogramming in goat. We found that H3K4me3 was an epigenetic barrier in goat nuclear reprogramming that and injection of Kdm5b … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 53 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…Yang et al (2020) reported that lnc2193 decreases the expression level of H3K4me3 and H3K9me3, thus affecting the porcine oocyte maturation. Deng et al (2021) have found that lnc_3712 regulates H3K4me3 and affects the development of goat embryos via repressing KDM5B. In our study, we analyzed Frontiers in Physiology frontiersin.org the expression profiles of representative epigenetic modification enzymes from the sequencing data and found that KDM5B, KDM5C, and SETD2 were upregulated after lncT knockdown.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Yang et al (2020) reported that lnc2193 decreases the expression level of H3K4me3 and H3K9me3, thus affecting the porcine oocyte maturation. Deng et al (2021) have found that lnc_3712 regulates H3K4me3 and affects the development of goat embryos via repressing KDM5B. In our study, we analyzed Frontiers in Physiology frontiersin.org the expression profiles of representative epigenetic modification enzymes from the sequencing data and found that KDM5B, KDM5C, and SETD2 were upregulated after lncT knockdown.…”
Section: Discussionmentioning
confidence: 80%
“…In the goat embryos, the knockdown of the lncRNA TCONS_00460156 significantly decreases the developmental rate (Deng et al, 2019). Deng et al (2021) showed that lnc_3712 impedes nuclear reprogramming via repressing KDM5B, and the microinjection of siRNA against lnc_137 causes development arrests (Deng et al, 2018). However, different from coding RNAs, lncRNAs are less conserved among species (Kern et al, 2018), and studies on lncRNA in pig embryo development are scarcer.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidences indicate that lncRNAs play assorted functions in the field of reproduction, such as spermatogenesis (Trovero et al, 2020), follicle growth (Ernst et al, 2018), oocyte maturation (Jiao et al, 2020;Yang et al, 2021), oocyte-to-embryo transition (Svoboda, 2017), embryonic development (Bouckenheimer et al, 2016) and others. Recent researches confirm that epigenetic modification can also be regulated by lncRNAs in oocytes and SCNT embryos (Yang et al, 2020;Deng et al, 2021). Based on above description, the present study applied the RNA-seq technique coupled with Smart-seq2 method to obtain the mRNA and lncRNA profiles of 2-cells, 4-cells and blastocysts derived from vitrified porcine cloned zygotes, which will directly lead to a deeper understanding of the molecular mechanism responsible for embryonic developmental impairment.…”
Section: Introductionmentioning
confidence: 94%
“…Beyond tackling food supply issues for a growing world population, the generation of transgenic animals for production of biopharmaceuticals presents another incentive for increased research efforts in vertebrates. One of the main methods used to this end is somatic nuclear cell transfer (SCNT) [ 240 ], which still faces the issues of low efficiency [ 241 ]. To address this challenge, a recent paper studied goat 8-cell SCNT embryos.…”
Section: Exploring the Ncrna Landscape Beyond Humansmentioning
confidence: 99%
“…The authors found the lncRNA lnc_3712 is crucial for the reprogramming efficiency by repressing the expression of the demethylase Kdm5b. The knockdown of lnc_3712 led to the increased expression of several vital embryonic genes and resulted in better development of goat SCNT embryos [ 241 ].…”
Section: Exploring the Ncrna Landscape Beyond Humansmentioning
confidence: 99%